-
For the circuit given below CMRR is given by:
-
-
1 R3(R1 + R2) + R2(R4 + R3) 2 R3(R1 + R2) - R1(R4 + R3) -
1 R3(R1 + R2) - R2(R4 + R3) 2 R3(R1 + R2) + R1(R4 + R3) -
1 R3(R1 + R2) - R2(R4 + R3) 2 R3(R1 + R2) - R1(R4 + R3) -
1 R3(R1 + R2) + R2(R4 + R3) 2 R3(R1 + R2) + R1(R4 + R3)
-
Correct Option: A
VB = Vi | ||||
R1 + R2 |
By using superposition principle.
Vo = – | . V2 + VB. | 1 + | |||||
R4 | R4 |
or Vo = – | . V2 + V1. | · | ............(i) | |||||||
R4 | R1 + R2 | R4 |
we know,
Vc = | .............(ii) | |
2 |
Vd = V1 – V2 …(iii)
from equations (ii) and (iii)
V1 = Vc + | .............(iv) | |
2 |
V2 = Vc – | .............(v) | |
2 |
Substituting these values in equation (i)
Vo = – | Vc – | + | Vc + | + | |||||||||||||
R4 | 2 | 2 | R1 + R2 | R4 |
or Vo = Vc | · | - | + | ...........(vi) | ||||||||||||||||
R1 + R2 | R4 | R4 | 2 | R1 + R2 | R4 | R4 |
Since, CMRR = | ||
AcM |
where AdM = | |Vd = 0 so from equation (vi) | |
Vd |
AdM | = | + | |||||||||
Vd | 2 | R1 + R2 | R4 | R4 |
and AdM = | |Vd = 0 | |
Vd |
AdM = | - | |||||||
R1 + R2 | R4 | R4 |
finally
CMRR = | ||||
2 | R3(R1 + R2) - R1(R4 + R3) |
Hence alternative (A) is the correct choice.